Reviews on Digital Payment System - Ramani, S (International Journal of Computer Sciences and Engineering, 2025)
this paper digital payments are using in developing countries. As the world has become globalized, it is tough to give the whole perspective of digital payments & how this is really helpful in our day-to-day life. This work will give maximum contribution to the knowledge and understanding the digital payment. It reveals that covered some basic points of digital payments & customer relationship management that goes to little higher level. So that it can give the overview on its structure & how it works. The customer can place orders at home to save their time. Digital payment systems have a very important role in E-commerce and they are used to complete E-commerce transactions. The purpose of this paper is to introduce current state, the challenges and future expectations of Digital Payment Systems. It depicts that the details of history of the e-commerce, the current situation of e-commerce and the methods of digital payment systems used in e-commerce. The results of the research show that now-a-days online payment systems are popular. All the respondents have experience on digital payments. Debit card (Visa or MasterCard) and Net Bank, PayPal, Payment wall ,Google Wallet, Mobile Money Wallets, Braintree, Stripe are the most popular digital payment systems, not only in countries. The second one is third-party digital payment systems. PayPal is more popular in the country. The two main factors contributing to choosing digital payment system are convenience and the quickness of transaction. Technical problems and vulnerability to cyber-crime are the main pros of digital payment system. Malware attack and financial issue are the main challenges of digital payment. Having a secure, reliable and trustworthy digital payment environment is important